Leadership and Sustainable Growth in Small, Micro and Medium-Sized Enterprises in Gauteng - Previledge Garikai Madhovi; Zeleke Worku; Mammo Muchie (The Institute of Academic Research and Publication (IARP), 2025)
South Africa faces problems due to the high rate of failure of start-up Small Medium and Micro sized Enterprises (SMMEs). The quest for enhancing leadership quality in South African SMMEs is vital for enabling SMMEs to grow and increase the Gross Domestic Product (GDP) of a country. Since the SMME sector is vital for creating jobs and livelihood for the poor, it deserves to be supported adequately. The purpose of the study is to assess the relationship between leadership quality and sustainable growth in SMMEs in the Gauteng province. Key attributes in terms of measuring growth are job creation, survival, and profitability among others. Data was gathered from the various SMMEs identified as the target population of this study, hence the design used was a cross-sectional one. The study made use of quantitative or statistical methods of data collection and analysis. The results revealed that there is correlation between the type of leadership and the attainment of sustainable growth. The implementation of ethical practices is crucial for the long-term sustainability of SMMEs, with ethical leadership being a key component of this process. Leaders who emphasize integrity, transparency, and responsible business practices can establish trust with various stakeholders, such as employees, customers, and investors.